Novo v poznavanju repertoarja starejših muzikalij cerkvene glasbe v Sloveniji - Škrjanc, Radovan (De musica disserenda, 2008)
The paper is a supplement to a previously published survey and analysis of the sacred music repertoire in eighteenth- and nineteenth-century Slovenia. It presents some research findings from several newly discovered eighteenth-century music manuscripts that belonged to the Ljubljana Cathedral archives.
Keywords: glasba; music; 18.st.; cerkveni repertoar; stolnice; Ljubljana; Slovenia; Slovenija